Chemistry of α-(arylhydrazono)-β-ketoaldehydes: Preparation and Chemical Reactivities - Gaber, Hatem M.; Gomha, Sobhi M.; Farghaly, Thoraya A.; Muhammad, Zeinab A.; Bagley, Mark C. (Current Organic Chemistry, 2018)
The following review provides up to date information about the recent progress in synthetic approaches and chemical reactivities to α-(arylhydrazono)-β-ketoaldehydes, mainly using N,N-dimethyl-β-ketoenamines as an efficient starting material. These α - (arylhydrazono)-β-ketoaldehydes have assured to be of biological interest and furnish an inlet to a new class of biologically active heterocyclic compounds for biomedical implementations. The data published until the end of 2017 have been covered.
Keywords: coupling reactions